Strategies of Passive Investment: Practical Aspect ("Journal "U". Economy. Management. Finance.", 2017)
The article considers passive investment from the point of view of a private investor. Authors offer their own method, which allows you to visually and quickly select the most attractive objects of investment in any industry.
Keywords: investment; stocks; bonds; multiplier; industry; securities market